Engineering Students’ Views on the Effectiveness of Peer Tutors in Scholars Assisting Scholars Program - Yang, Yang; Grauer, Bette; Thornburg, Jennifer; Betz, Amy (My University, 2020)
In engineering education, retaining engineering students in the first two years of college is a critical issue when the attrition rate has been persistently high. Peer tutoring and supplemental instruction are widely used methods to help first year students and sophomores succeed in challenging courses in universities. Research has shown that peer tutoring improves academic outcomes such as achieving higher GPAs, higher retention rates, and improving student connectedness. In an earlier study we examined whether and to what degree a peer tutoring and supplemental instruction program called Scholars Assisting Scholars, SAS, implemented in a college of engineering facilitated student academic performance in a specific Calculus course. In this follow-up study, we focused on the impact of the peer tutoring and supplemental instruction program on students who utilized the peer tutoring program across a wide range of core courses.